'CREATE SOMETHING NEW' THROUGH ENTREPRENEURSHIP TO REMAIN RELEVANT - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 15 January 2017 Teaching and learning activities need to change to remain relevant and students should be able to reach a certain level in their learning achievements to create something new from the knowledge gained.